The role of hydration properties of soluble dietary fibers on glucose diffusion. (October 2022) - Miehle, Elisabeth; Haas, Melanie; Bader-Mittermaier, Stephanie; Eisner, Peter
Abstract: The inclusion of high levels of dietary fibers in meals is associated with a reduction of the glucose release in the human gut. However, the commonly considered viscous effects of soluble dietary fibers (SDF) are insufficient to explain the altered glucose release. In this study, we therefore, aimed to investigate the effect of hydration properties (i.e. water holding capacity (WHC), amount of bound water, osmotic pressure) on in vitro glucose diffusion along an osmotic gradient using a side-by-side cell system. For this, five types of SDF (low-and high-methylester pectin, xanthan gum, locust bean gum, carboxymethyl cellulose) and citrus fiber comprising 16% of soluble fibers and 72% of insoluble fibers were used. The diffusivity of glucose decreased significantly in all fiber solutions at low concentrations, which were above the critical concentration for SDF. We observed a strong correlation between the hydration properties of SDF and the glucose diffusivity revealing correlation coefficients ranging from R 2 = 0.94 for WHC to R 2 = 0.81 for the amount of bound water and R 2 = 0.79 for water mobility. The partly insoluble swollen citrus fiber exhibited a gel-like behavior, which resulted in reduced glucose diffusivity. Therefore, we were able to show that – besides viscosity and molecular weight – the hydration properties, particularly WHC, the amount of bound water and water mobility should be investigated for the characterization of soluble dietary fibers and their impact on glucose diffusion in an osmotic-driven system. Graphical abstract: Image 1 Highlights: Fiber solutions above the c* significantly decreased the diffusion of glucose. Hydration properties of SDF strongly correlated (up to R 2 = 0.94) with D of glucose. High hydration properties of SDF reduce D under in vitro setup with applied osmoticum. Gel-like behavior of citrus fiber decrease D of glucose.